Applications of Remote Sensing in Coastal Areas - Topouzelis, Konstantinos; Papakonstantinou, Apostolos; Singha, Suman; Li, XiaoMing; Poursanidis, Dimitris (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Coastal areas are remarkable regions with high spatiotemporal variability. A large population is affected by their physical and biological processes-resulting from effects on tourism to biodiversity and productivity. Coastal ecosystems perform several critical ecosystem services and functions, such as water oxygenation and nutrients provision, seafloor and beach stabilization (as sediment is controlled and trapped within the rhizomes of the seagrass meadows), carbon burial, as areas for nursery, and as refuge for several commercial and endemic species. Knowledge of the spatial distribution of marine habitats is prerequisite information for the conservation and sustainable use of marine resources. Remote sensing from UAVs to spaceborne sensors is offering a unique opportunity to measure, analyze, quantify, map, and explore the processes on the coastal areas at high temporal frequencies. This Special Issue on "Application of Remote Sensing in Coastal Areas" is specifically addresses those successful applications-from local to regional scale-in coastal environments related to ecosystem productivity, biodiversity, sea level rise.